1988
DOI: 10.1016/0266-7681(88)90169-6
|View full text |Cite
|
Sign up to set email alerts
|

Beau's lines following hand trauma

Abstract: Six cases are described of Beau's lines (transverse grooves in the fingernails) developing after injuries to the hand involving damage to nerves and flexor tendons. The literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Tosti et al [7] postulated that nerve injury could produce these nail abnormalities. Ward et al [2] and Harford et al [3] however proposed that nerve lesions do not account for the appearance of Beau's lines since they did not always correlate. Furthermore, neither Beau's lines nor pyogenic granuloma were described in 679 patients suffering from denervation as a result of spinal cord injury [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tosti et al [7] postulated that nerve injury could produce these nail abnormalities. Ward et al [2] and Harford et al [3] however proposed that nerve lesions do not account for the appearance of Beau's lines since they did not always correlate. Furthermore, neither Beau's lines nor pyogenic granuloma were described in 679 patients suffering from denervation as a result of spinal cord injury [8].…”
Section: Discussionmentioning
confidence: 99%
“…The role of immobilization of the limb in the pathogenesis of Beau's lines and pyogenic granuloma is currently unknown but was reported in almost all the cases in the literature, including ours [2][3][4]7]. Dawber [9] has suggested that immobilization could slow down the fingernail growth rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They appear several weeks after the nail dam age. Beau's lines have been described in patients with me tabolic disturbances, such as zinc deficiency in liver cirrho sis [9], various systemic diseases including diabetes melli tus [10], following hand injuries accompanied by damage of nerves and tendons [11], and even in infants soon after birth, due most probably to intrauterine damage [8]. En docrine disorders, other than diabetes, also have been sug gested as a possible cause.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are usually bilateral, unilateral (one hand or foot) Beau's lines may uncommonly occur. Unilateral Beau's lines have been described by Ward (1), Roberts (2), Price (3), and Harford (4) following injury of the wrist, hands, forearm, and elbow. Because their injured areas were the proximal portions of the nail folds, transverse depressions of the nails could occur in all the fingernails of the affected extremity.…”
Section: Introductionmentioning
confidence: 99%